Identification of novel epithelial ovarian cancer loci in women of African ancestry. Issue 11 (8th October 2019) - Manichaikul, Ani; Peres, Lauren C.; Wang, Xin‐Qun; Barnard, Mollie E.; Chyn, Deanna; Sheng, Xin; Du, Zhaohui; Tyrer, Jonathan; Dennis, Joseph; Schwartz, Ann G.; Cote, Michele L.; Peters, Edward; et al.
Abstract : Women of African ancestry have lower incidence of epithelial ovarian cancer (EOC) yet worse survival compared to women of European ancestry. We conducted a genome‐wide association study in African ancestry women with 755 EOC cases, including 537 high‐grade serous ovarian carcinomas (HGSOC) and 1, 235 controls. We identified four novel loci with suggestive evidence of association with EOC ( p  < 1 × 10 −6 ), including rs4525119 (intronic to AKR1C3 ), rs7643459 (intronic to LOC101927394 ), rs4286604 (12 kb 3′ of UGT2A2 ) and rs142091544 (5 kb 5′ of WWC1 ). For HGSOC, we identified six loci with suggestive evidence of association including rs37792 (132 kb 5′ of follistatin [ FST ]), rs57403204 (81 kb 3′ of MAGEC1 ), rs79079890 ( LOC105376360 intronic), rs66459581 (5 kb 5′ of PRPSAP1 ), rs116046250 ( GABRG3 intronic) and rs192876988 (32 kb 3′ of GK2 ). Among the identified variants, two are near genes known to regulate hormones and diseases of the ovary ( AKR1C3 and FST ), and two are linked to cancer ( AKR1C3 and MAGEC1 ). In follow‐up studies of the 10 identified variants, the GK2 region SNP, rs192876988, showed an inverse association with EOC in European ancestry women ( p = 0.002), increased risk of ER positive breast cancer in African ancestry women ( p = 0.027) and decreased expression of GK2 in HGSOC tissue from African ancestry women ( p = 0.004). A European ancestry‐derived polygenic risk score showed positive associations with EOC and HGSOC in women of African ancestry suggesting shared genetic architecture. Our investigation presents evidence of variants for EOC shared among European and African ancestry women and identifies novel EOC risk loci in women of African ancestry. Abstract : What's new? Women of African ancestry have lower incidence of epithelial ovarian cancer (EOC) yet worse survival compared to women of European ancestry. To date, genome‐wide association studies (GWAS) have identified 30 common, low‐penetrant EOC susceptibility alleles. However, most studies were restricted to European ancestry women, and it remains to be determined whether there is any concordance among women of African descent. In this first GWAS conducted in women of African ancestry, the authors report ten novel associated SNPs. The results also suggest there may be some shared genetic architecture between women of European and African ancestry for susceptibility to ovarian cancer.